Membrane filtration characteristics in membrane-coupled activated sludge system: The effect of floc structure on membrane fouling - Chang, IS; Lee, CH; Ahn, KH (TAYLOR & FRANCIS INC, 1999)
The membrane-coupled activated sludge (MCAS) process has many advantages over the conventional activated sludge system, but the inherent membrane fouling problem still remains to be solved. However, it is not yet advanced enough to understand the reliable fouling mechanism. The strength of the MCAS process lies in the almost complete removal of suspended solids from the activated sludge broth. But it has made us overlook the effect of sludge morphology and physiology on membrane flux which is one of the key factors in deciding the economical feasibility of the MCAS system. The aim of this study was to investigate membrane filtration characteristics in the MCAS process, especially to correlate floc structures of the activated sludge with membrane fouling. A series of ultrafiltrations with both hydrophilic and hydrophobic membranes using the stirred batch cell system was performed to assess flux behavior according to the floc structures of the activated sludges (normal, pinpoint, and bulking activated sludge). The order of fouling tendency was found to be normal sludge < pinpoint sludge < bulking sludge. Also, all the membranes behaved in the same way. The cake layer resistance (R-c) made up most of the total resistance (R-t), but the fouling resistance (R-f) was negligible in any floc structure. The key factors controlling the R-c were the shape and size of the activated sludge flocs and the porosity of the cake layer accumulated on the membrane surface. The hydrophobic membrane showed a greater fouling tendency than the hydrophilic membrane regardless of the microbial floc structures. The difference in fouling tendency between the two membranes was attributed to the hydrophobic interactions between the membrane and floc surfaces.
Keywords: WASTE-WATER TREATMENT; SOLID-LIQUID SEPARATION; NITROGEN REMOVAL; BIOREACTOR; PERFORMANCE; ULTRAFILTRATION; FLUX